Ethnic and Adipose Depot Specific Associations Between DNA Methylation and Metabolic Risk - Pheiffer, Carmen; Willmer, Tarryn; Dias, Stephanie; Abrahams, Yoonus; Louw, Johan; Goedecke, Julia H. (Frontiers in Genetics, 2020)
Background Metabolic risk varies according to body mass index (BMI), body fat distribution and ethnicity. In recent years, epigenetics, which reflect gene-environment interactions have attracted considerable interest as mechanisms that may mediate differences in metabolic risk. The aim of this study was to investigate DNA methylation differences in abdominal and gluteal subcutaneous adipose tissues of normal-weight and obese black and white South African women. Methods Body composition was assessed using dual-energy x-ray absorptiometry and computerized tomography, and insulin sensitivity was measured using a frequently sampled intravenous glucose tolerance test in 54 normal-weight (BMI 18-25 kg/m2) and obese (BMI ≥ 30 kg/m2) women. Global and insulin receptor (INSR) DNA methylation was quantified in abdominal (ASAT) and gluteal (GSAT) subcutaneous adipose depots, using the Imprint methylation enzyme-linked immunosorbent assay and pyrosequencing. INSR gene expression was measured using quantitative real-time PCR. Results Global DNA methylation in GSAT varied according to BMI and ethnicity, with higher levels observed in normal-weight white compared to normal-weight black (p=0.030) and obese white (p=0.012) women. Pyrosequencing of 14 CpG sites within the INSR promoter also showed BMI, adipose depot and ethnic differences, although inter-individual variability prevented attainment of statistical significance. Both global and INSR methylation were correlated with body fat distribution, insulin resistance and systemic inflammation, which were dependent on ethnicity and the adipose depot. Adipose depot and ethnic differences in INSR gene expression were observed. Conclusion We show small, but significant global and INSR promoter DNA methylation differences in GSAT and ASAT of normal-weight and obese black and white South African women. DNA methylation in ASAT was associated with metabolic risk in white women, whereas in black women DNA methylation in GSAT was associated with metabolic risk. Our findings suggest that GSAT rather than ASAT may be a determinant of risk in black women and provide novel evidence that altered DNA methylation within adipose depots may contribute to ethnic differences in body fat distribution and cardiometabolic risk.